Clinico-epidemiological study of chronic leg ulcers in a tertiary care referral center from Tamil Nadu, India - Kaliyaperumal, Damayandhi; Jagadeeshkumar, Govardhan; Kanagaraj, Preethi; Chandran, Vijayabhaskar (International Journal of Research in Dermatology, 2021)
Background: Leg ulcer is a common ailment of elderly presented with complex dermatological conditions. It may occur as a sequel to infection, malignancy, adverse drug reaction, trauma and hematological disorders. The paucity of data on the prevalence and outcome of the chronic leg ulcer in India served as a basis to conduct this clinico-epidemiological study. To study the prevalence of leg ulcers in a tertiary care referral hospital. Methods: In this cross-sectional study, 100 patients with leg ulcer attending the dermatology OPD at Madras medical college, Chennai, were enrolled after obtaining their consent. Detailed case history of each patient was recorded. Routine clinical investigations, Doppler study and culture were done to detect associated complications. In this study, 58 males and 42 females, with the mean age of 42.01±14.302 years, mean duration of leg ulcer of 17.79±29.87 months were recruited. Results: Venous ulcer (37%) was the most prevalent type of leg ulcer recorded in our study. Doppler study revealed that the 31% of venous ulcers patients developed perforator incompetence. Staphylococcus aureus was the major microbe isolated from the lesions (27%). Conclusions: Chronic leg ulcers are very common in elderly patients and venous ulcer being the most common. Doppler is an effective tool for the assessment of disease severity of venous ulcers and aided in offering the adequate management of the disease. Diagnosis of underlying causes such as pyoderma gangrenosum, autoimmune diseases, malignancies and bacterial culture from the wound will be helpful for the management of the disease.